Deteksi Kontaminasi Toxoplasma gondii Pada Daging Kambing di Bali dengan Primer BAG1 - Santoso, Jemima Lewi; Adrianto, Hebert; Tandean, Victor Setiawan; Yuwono, Victor Kurniawan; Santoso, Novian Budi; Juliasih, Ni Njoman; Sayogo, William; Bravimasta, Bracovanca Diwayestara; Firmanto, Ian Ardhiya; Afifah, Balqis (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Toxoplasmosis is an infection caused by the protozoan parasite Toxoplasma gondii. One of the transmission routes of T. gondii infection is the consumption of undercooked meat. Goats are an important source of income for farmers in Bali and have been reported to have the potential to carry T. gondii. The aim of this study was to detect the presence of Toxoplasma gondii contamination in goat meat in Kuta and Ubud, Bali, using molecular methods with BAG1 primers. Meat samples obtained from markets in Kuta and Ubud were sectioned, followed by extraction of T. gondii DNA, amplified by PCR, and electrophoresed on a 1% agarose gel. The resulting amplification products were approximately 470 base pairs in size. The study results indicated that goat meat was only successfully obtained from the Kuta market. Examination for the presence of T. gondii parasite in goat meat from the Kuta market targeting the BAG1 gene yielded all negative results (100%). Hygiene in goat husbandry should be maintained and even improved. Meat sold in markets or stores must be routinely inspected to ensure safety. Additionally, meat should be cooked at sufficiently high temperatures, and consumption of undercooked or rare meat should be avoided